2023
DOI: 10.1021/acscatal.3c04171
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Conversion of Fatty Acids into Terminal Alkenes by an Integral Membrane Enzyme, UndB

Tabish Iqbal,
Subhashini Murugan,
Kalpana Rajendran
et al.

Abstract: Biosynthetically produced 1-alkenes hold immense value as green alternatives to fossil fuels and find widespread applications in the polymer, lubricant, and detergent industries. UndB is the only known membrane enzyme capable of converting fatty acids into 1-alkenes with unprecedented in vivo titers. However, despite diverse applications, UndB has remained poorly understood since its discovery nearly a decade ago. We present here insights into the molecular basis of UndB catalysis and the mechanism of the UndB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Our study sheds light on the mechanism of didecarboxylation of dicarboxylic acids by UndB, suggesting that the enzyme does not decarboxylate both carboxylic acid moieties simultaneously but rather in a stepwise fashion through the intermediacy of a mono-decarboxylated acid. This could be further supported by our recently proposed reaction mechanism of UndB, which suggests that the fatty acid binds to the active site of UndB by coordinating with the active site iron through its carboxyl group (Iqbal et al, 2023). The binding of two carboxylate groups at the diiron center would not be feasible and would hinder the hydrogen abstraction from the C-3 position of fatty acids.…”
Section: Insights Into Undb-catalyzed Decarboxylation Of Dicarboxylic...mentioning
confidence: 69%
See 3 more Smart Citations
“…Our study sheds light on the mechanism of didecarboxylation of dicarboxylic acids by UndB, suggesting that the enzyme does not decarboxylate both carboxylic acid moieties simultaneously but rather in a stepwise fashion through the intermediacy of a mono-decarboxylated acid. This could be further supported by our recently proposed reaction mechanism of UndB, which suggests that the fatty acid binds to the active site of UndB by coordinating with the active site iron through its carboxyl group (Iqbal et al, 2023). The binding of two carboxylate groups at the diiron center would not be feasible and would hinder the hydrogen abstraction from the C-3 position of fatty acids.…”
Section: Insights Into Undb-catalyzed Decarboxylation Of Dicarboxylic...mentioning
confidence: 69%
“…Previous studies with the whole cells expressing UndB showed that the enzyme converts a wide range of fatty acids (chain length C6‐C18) into the corresponding 1‐olefins (Rui et al, 2015). Recent studies have demonstrated that UndB prefers C12‐fatty acid (lauric acid) to longer‐or shorter‐chain fatty acids (Iqbal et al, 2023; Rui et al, 2015). We recently reported that cyanobacterial ( Synechococcus elongatus ) ferredoxin and ferredoxin reductase support the highest in vitro activity of UndB (Iqbal et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations